Methods Of Prevention And Treatment Of Postoperative Complications In Infants Undergoing Surgery In The First Days Of Life - Badleeva, Maria Vladimirovna; Savina, Aleksandra Igorevna; Rastunin, Vladimir Vasilyevich; Rakhamimova, Sheron Raufovna; Plekhanova, Svetlana Vladislavovna; Vorobeva, Alexandra Olegovna; Yundunova, Oyuna Vladimirovna (Journal of Neonatal Surgery, 2025)
This article deals with the topical issues of prevention and treatment of postoperative complications in infants who underwent surgical interventions in the first days of life. The specifics of management of newborns with congenital pathologies of various etiologies requiring immediate surgical intervention are revealed, and modern possibilities of intensive care and resuscitation support of such patients are analyzed. The importance of interdisciplinary interaction between paediatric surgeons, neonatologists, anaesthesiologists-resuscitators and specialists in the field of clinical pharmacology is emphasized, which allows timely detection and correction of early manifestations of septic, respiratory, haemodynamic and metabolic disorders. The work substantiates the need for an integrated approach to diagnosis and therapy, which involves the use of modern monitoring methods, adequate respiratory support, individualized nutritional support, strict control of water-electrolyte balance and a well-thought-out antibacterial policy, taking into account local strains of microorganisms. The etiopathogenesis of the most frequent postoperative complications is highlighted, and data on the effectiveness of extended intensive care protocols are presented. The study is based on the analysis of clinical cases of 162 children who received surgical care in the first three days of life and demonstrates statistically proven benefits of comprehensive measures aimed at preventing infections and functional disorders. Risk factors associated with gestational age, body weight, intrauterine development and the presence of comorbid conditions are highlighted. In the context of the global development of neonatal surgery, the paper emphasizes the contribution of modern technologies and treatment methods in improving the prognosis and quality of life of newborns undergoing early surgical interventions.